Various Prothrombin Complex Concentrates and their Effect on Coagulation and Fibrinolysis In Vivo - Hedner, U; Nilsson, I.M; Bergentz, S.-E (Thrombosis and Haemostasis, 1976)
Thromboembolic complications occurring in patients treated with factor IX concentrates have been reported. To study the thrombogenicity various types of factor IX concentrates (50 or 100 units F. IX/kg bodyweight) have been infused in dogs. As control albumin was given. The various components of the coagulation and fibrinolytic system have been assayed before the infusion and at various intervals after the end of infusion (0, 1,4 and 24 hrs). Konyne resulted in marked activation of the coagulation process with decrease of platelets, fibrinogen, F. VIII and appearance of FDP and positive ethanol gelation test. Pro thro mplex and Pre-conativ gave no significant changes. Preconativ is prepared without addition of heparin during the procedure.